Canopy humidity and irrigation regimes interactively affect rice physiology, grain filling and yield during grain filling period - Le Chen; Xueyun Deng; Hongxia Duan; Xueming Tan; Xiaobing Xie; Xiaohua Pan; Lin Guo; Tao Luo; Xinbiao Chen; Hui Gao; Haiyan Wei; Hongcheng Zhang; et al. (Agricultural Water Management)
Rice growth and yield performance are closely related to climate variables and soil water regimes. Therefore, in this study, normal humidity (NH) and high humidity (HH) treatments of rice canopy were performed and combined with continuous flooding (CF), alternate wetting and drying (AWD), and drought cultivation (DC). The changes in crop physiology were monitored in a 2-year artificial intelligence greenhouse experiment. Creating HH lowered the seed setting rate, grains per panicle and yield relative both under AWD and CF, but was rather beneficial under DC. The HH decreased the soil plant analysis development (SPAD) parameter and net photosynthetic rate while leaf surface temperature, antioxidant enzyme activity and malondialdehyde (MDA) level got increased. Additionally, HH increased the contents of abscisic acid (ABA), gibberellin (GA3) and jasmonic acid (JA) and the activities of key starch synthase, increasing the grain filling rate while shortening the active filling duration. The rice yield of AWD treatment under HH condition was the highest, mainly because the net photosynthetic rate, pollen viability and key starch synthase activity were maintained at a higher level. The AWD measures can be adopted to maintain high rice yields under high humidity conditions, while yields can be improved by increasing canopy humidity under persistent drought conditions.